Economic Reforms, Growth, and Governance : The Political Economy Aspects of Bangladesh's Development Surprise - Mahmud, Wahiduddin; Ahmed, Sadiq; Mahajan, Sandeep (World Bank, Washington, DC, 2017)
Bangladesh has in recent decades achieved reasonably rapid economic growth and significant progress in social development indicators despite many impediments: the desperate initial conditions after gaining independence, lack of resources, natural disasters, widespread corruption, and a record of systemic governance failure. By identifying the sources of growth stimulus and the drivers of social transformation, the paper addresses what it calls Bangladesh's development surprise. The policy-making process is analyzed as the outcome of incentives created by patronage politics as opposed to the compulsion for the government to play an effective developmental role. The paper examines the governance-growth nexus as affecting the pace and quality of growth and its inclusiveness. If the governance environment has been barely adequate to cope with an economy breaking out of stagnation and extreme poverty, it increasingly may prove a barrier to putting the economy firmly on a path of modernization and global integration. Bangladesh's experience also shows that it is possible to make rapid initial progress in many social development indicators by creating awareness through successful social mobilization campaigns and by reaping the gains from affordable low-cost solutions. Further progress, however, will require increased public social spending and improved quality of public service delivery.